Development and characterization of recycled carbon-kenaf filled cardanol hybrid composites - Dashtizadeh, Zahra (2018)
Kenaf fibers have shown a great potential to be a replacement for synthetic fibers due to their high specific strength, light weight, low cost and renewable source. However, like all other natural fibers, the mechanical properties of kenaf fiber are highly affected by its hydrophilic nature. Researchers suggest chemical treatment for fibers to improve its strength and compatibility with a variety of resins. In this research, the results indicate that alkaline and silane treatment with specific concentration increase single fiber tensile strength. The increment is higher for alkaline treatment compared to silane treatment. However, tensile strength of the composites made of treated kenaf fiber and cardanol (bio-phenolic derived from cashew nut shell liquid, CNSL) composite showed small improvement as compared to untreated kenaf fiber and cardanol composites. Different fiber volume fractions were fabricated, 0%w Kenaf ,30%w Kenaf, 40%w Kenaf, 50%w Kenaf and 60%w Kenaf. Then the mechanical, thermal, physical, chemical and flammability properties of the specimens were studied. The Results showed that composite with 50%w Kenaf shows the highest tensile and flexural strength, while impact strength increased up to 60%w kenaf. For further improvement of the mechanical properties, recycled carbon was used to fabricate the hybrid composites. Hybridization with recycled carbon enhanced the mechanical properties of cardanol/ kenaf composites. Also, hybridization of treated kenaf fibers with carbon fibers demonstrated higher mechanical properties. In addition, thermal characterizations of the specimens indicate that cardanol improved the thermal stability of kenaf also hybridization with recycled carbon further improves the thermal stability of the specimens. Flammability UL 90HB test determines the flame retardancy property of all specimens. It was observed that the peak of tan δ for cardanol was higher than all other specimens which also agreed with the previous results that showed cardanol had a lower damping property and was more brittle than the kenaf/cardanol composites, the shift of tan δ and reduction of the absolute value indicate the interaction between kenaf and cardanol which enhanced the mechanical properties of the kenaf/cardanol composites. It was also observed that the specimen with higher fiber volume fraction showed the lower tan δ and higher damping property.